Mediação pedagógica na formação de professores : um estudo da disciplina de Libras - Lucas, Karem Adriana (2018)
Need for communication and interaction between the subjects stimulated the creation of different forms of language, among them language, a code formed by grammatical rules and used by individuals in the community who created it. Signal languages have emerged as well as oral/auditory modalities to address this need for communication and interaction. In this sense, the Brazilian Language of Signals (Libras) is included as a compulsory subject in the curricular structure of undergraduate courses. From these aspects, this work aimed analyze pedagogical mediation in the discipline of Libras offered in the teacher training courses of the Federal University of Mato Grosso (UFMT), Cuiabá campus. In this way, the legal and theoretical aspects regarding Libras, language, language and the Mediated Learning Experience (MEA) are addressed. The study is characterized as a quantitative-qualitative approach in the descriptive and exploratory perspective, with the premise that mediation occurs in all contexts and has special characteristics that students can identify in the discipline of Libras. The data were collected through a questionnaire elaborated based on the MEA theory, evocation of words of the study theme and characteristics of the participants. Eightythree students aged 20 to 30 years participated of randomly selected undergraduate courses (Chemistry, Pedagogy, History, Philosophy, Geography, Physical Education, Music, Biological Sciences, Language: Portuguese and Spanish Qualification and Respective Literatures, and Language: Qualification in Portuguese and Literature), after having completed 75% of the hours of the discipline of Pounds. The results show that: a) criteria with a high level of evidence (above 70%): Intentionality, Mediation of Meaning, Mediation of feeling of competence, Mediation of behavior of sharing; b) criteria with a lower level of evidence: Reciprocity, Transcendence, Mediation of regulation and behavior control, Mediation of the search for challenge, novelty and complexity and Mediation of the consciousness of being a modifiable entity; c) most evoked words: deaf, signs, inclusion. The MEA allows basing the action of teachers in the classroom and may be better suited to different contexts.